THE EFFECT OF WORK TRAINING, DISCIPLINE AND MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. BRAJA MUKTI CAKRA - Latif Maulana; Muhammad Richo Rianto; Eri Bukhari (Draf Solusi Indonesia, 2023)
This research is a quantitative study using a questionnaire addressed to employees of PT. Braja Mukti Cakra. Sampling in this study was carried out by distributing questionnaires with a total sample of 80 respondents. The design used in this study is hypothesis testing using the SmartPLS 4.0 statistical tool.The results of this study provide an explanation that the variables of job training and work discipline have a positive effect on the performance of employees of PT. Braja Mukti Cakra. However, the variable of work motivation does not affect the performance of PT. Braja Mukti Cakra employees, in this study it shows that work motivation is not the main consideration in employee performance